2005
DOI: 10.1557/jmr.2005.0090
|View full text |Cite
|
Sign up to set email alerts
|

Deformation-induced nanocrystallization: A comparison of two amorphous Al-based alloys

Abstract: Using conventional and high-resolution transmission electron microscopy (HRTEM), the effects of rolling at room temperature on the microstructures of amorphous Al 90 Fe 5 Gd 5 and Al 86.8 Ni 3.7 Y 9.5 were compared. In rolled Al 90 Fe 5 Gd 5 , nanocrystallites were observed at shear bands, whereas none were observed in rolled Al 86.8 Ni 3.7 Y 9.5 . When HRTEM was combined with with Fourier transform filtering, nanoscale, low-density defects were imaged. In Al 90 Fe 5 Gd 5 , the shear bands contain few defects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…17,18 Unlike some Al-rich metallic glasses, this alloy does not crystallize upon room-temperature plastic deformation. It exhibits significant anelastic deformation at room temperature, enabling us to conduct stable, high resolution, measurements for durations of 1 s-3 Â 10 7 s. Our simple experiments provide valuable information on STZ properties.…”
Section: Introductionmentioning
confidence: 92%
“…17,18 Unlike some Al-rich metallic glasses, this alloy does not crystallize upon room-temperature plastic deformation. It exhibits significant anelastic deformation at room temperature, enabling us to conduct stable, high resolution, measurements for durations of 1 s-3 Â 10 7 s. Our simple experiments provide valuable information on STZ properties.…”
Section: Introductionmentioning
confidence: 92%
“…[18,[30][31][32][33][34][35] Unlike crystalline materials, metallic glasses exhibit shear softening and the excessive propagation of individual shear bands may cause premature fracture. Shear banding may also lead to the local structural changes within a shear band, such as nanocrystallization, [36][37][38][39][40][41][42][43][44][45] nanovoids, [41][42][43][44][45] and excessive free volume. [46,47] However, up until now, it has not been explained conclusively why shear banding can cause such changes to the structure and property of metallic glasses.…”
Section: Introductionmentioning
confidence: 99%
“…28 After Chen et al 29 first reported the formation of nanocrystallites in the shear bands of amorphous Al-based alloys observed with TEM, there has been much experimental evidence for nanoscale crystallites formed in the vicinity of shear bands, fracture surfaces, nanoindentation, and in tensile and bending tests at room temperature or below. [30][31][32] In the homogeneous flow region, de Hey et al further associated the glass transition behavior in the DSC trace of the deformed specimen with the amount of free volume and used it to explain the deformation behavior of Pdand La-based alloys. 7,23,24 Heggen et al used compression creep testing at constant stress and during jump stress to study the structural relaxation and disordering during the high-temperature deformation of a Pd-NiCu-P alloy, from the perspective of free volume creation and annihilation.…”
Section: Introductionmentioning
confidence: 99%